Where Did You Go Today? A Brief History of Narrative Space. Where Will You Go Tomorrow? The Future of Narrative Space - Haynes, Sarah (Universitas Multimedia Nusantara, 2024)
Whilst location and setting, mise en scene, have always been key elements of moving image, since the advent of computing, space has become a more prominent feature. This paper will consider the spaces in which moving image narratives play, the fictional spaces they conjure and the effect of technologies on the construction, delivery and reception of narrative space. Manovich’s characterization of the digital experience as, ‘spatial wandering,’ (2001, p49) echoed Murray’s declaration that, ‘Digital media are spatial.’ (Murray quoted by Ryan, 2016, p100). Narrative has always been immersive. The transporting nature of narrative provides one of its key pleasures. ‘Relax. Concentrate. Dispel every other thought. Let the world around you fade,’ Calvino, (1979, p3) invites his readers to lose themselves in his novel, If On A Winters Night A Traveler, beginning a journey into a narrative that explores the very idea of immersion. Like the first establishing shot of a film, Calvino instructs his readers to imagine a train station, positioning them in a scene created in their minds eye. ‘Arguably the best stories are those which you are lost in.’ (Weedon, 2018, p50). Millennia ago, sitting around the campfire, storytellers would ignite the imaginations of their listeners, conveying them to fantasy spaces, historical landscapes, fabled events, carried there by their own visions. Successive technologies have separated storytellers from their audience, through the alphabet, print, photography, film, and computer screens. This paper will look to a future of narrative space, when stories spill out of the screen, providing embodied experiences, in headsets, projection mapped onto locations, in mixed and augmented reality scenarios, mediated by artificial intelligence. Are we moving into a new narrative age following Manovich’s ages of the frame, proscenium arch, cinema and computer screen, one in which we leave the frame behind and step into the narrative space? This paper posits that the introduction of digital processes in the production and consumption of moving image afford new experiences of narrative space for both producers and consumers of moving image culture. Keywords: narrative space; storytelling; virtual reality; virtual production